The results of a non-destructive site exploration and a rescue excavation at the site of Pusztaszabolcs-Dohányos völgy északi part - Váczi, Gábor; Rupnik, László; Czajlik, Zoltán; Mesterházy, Gábor; Bittner, Bettina; Fülöp, Kristóf; Lönhardt, Denisa M.; Szabó, Nóra (Dissertationes Archaeologicae, 2021)
It is only possible in rare cases to compare aerial photographs, fieldwork data, surveys of two types of magnetometer measurements, and metal detector surveys of a site with the results of a previous rescue excavation. The cooperation of the Castle Headquaters Integrated Developement Centre, the Szent István Király Museum of Székesfehérvár, and the Institute of Archaeological Sciences at the Eötvös Loránd University made the discovery of the multi-period site on the outskirts of Pusztaszabolcs possible.